Two new species of philometrid nematodes (Nematoda: Philometridae) in Epinephelus coioides (Hamilton, 1822) from the South Bali Sea, Indonesia - Dewi, Kartika; Palm, Harry W. (Zootaxa, 2013)
Based on light and scanning electron microscopy, two new species of philometrid nematodes, Spirophilometra endangae sp. nov. and Philometra epinepheli sp. nov. (Nematoda: Dracunculoidea: Philometridae) are described from Epinephelus coioides (Hamilton, 1822) (Perciformes: Serranidae) from the South Bali Sea, Indonesia. Spirophilometra endangae sp. nov. was isolated from the fins of E. coioides. The new species can be distinguished from the most closely related S. eichleri Parukhin, 1971 by a larger total body length and the site of infection in the host. The new species differs from S. centropomi (Caballero, 1974) also in the larger body size of the gravid females and the site of infection in the host. S. en-dangae sp. nov. differs from S. pacifica (Moravec, Santana-Pineros, Gonzales-Solis & Torres-Huerta, 2007) in the struc-ture and arrangement of the spines on the middle part of the body, the infection site of the worm, the type host and the zoogeographical host distribution. Philometra epinepheli sp. nov. differs from all other Philometra spp. congeners so far recorded from Ephinepelus groupers in the total body length and the site of infection. This is the first opercula-infecting species of Philometra described from the fish family Serranidae.